CONTEXTUAL SEMANTIC ISSUES IN THE TRANSLATION OF AGRICULTURAL TERMS IN ENGLISH AND UZBEK LANGUAGES (Ta'limning zamonaviy transformatsiyasi, 2025)
Abstract: This thesis helps to investigate the intricate challenges posed by contextual semantics in the translation of agricultural terminology between the English and Uzbek languages. Agriculture, a foundational sector for the economy and cultural heritage of Uzbekistan, necessitates precise and contextually sensitive translations for effective international collaboration, robust academic discourse, and informed policy formulation. The translation of agricultural terminology is particularly complex according to the inherent cultural, linguistic, and contextual disparities between English and Uzbek. This research tries to identify prevalent issues, including semantic incongruities, culturally embedded terms lacking direct equivalents, and the profound impact of context on meaning, which can result in significant losses in translational accuracy and the suppression of vital cultural nuances.